Audyt wewnętrzny w administracji publicznej na przykładzie Urzędu Wojewódzkiego w Łodzi - Szydłowski, Cezary (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The idea of the internal audit is relatively new in the polish public administration. Introduction of this process was imposed by the european law on the one hand and on the other hand by the requirement to rationalize activities and management capacity of the public administration.The author (Mr. Cezary Szydłowski - the qualified Auditor in the Internal Audit Unit, The Lodz Voivodship Office) draws our attention to the main differences between a classical control and an internal audit. Furthermore he explains and describes in details all characteristics of the internal and external audit. Finally he focuses on the organization of the internal audit in the Lodz Voivodship office.Traditionally the internal audit was concentrated primarily on evaluation of the internal control system in institution. The new approach is based on a risk analysis, which is described as the elementary tool of planning and management. The author emphasizes the importance of this modem audit in the management of public resources, especially a significant role which the internal audit will play in the process of the European Union Funds' management. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 742-754